A Handbook of Applied Biopolymer Technology Synthesis, Degradation and Applications. - Sharma, Sanjay K.; Mudhoo, Ackmez; Clark, James H.; Kraus, George A.; Osswald, Tim A.; Garcia-Rodriguez, Sylvana; Teramoto, Naozumi; Rai, Rajana; Roy, Ipsita; P. M., Visakh; Thomas, Sabu; Pothan, Laly A.; et al. (RSC green chemistry series., 2011)
Annotation